Economical Performances and Cholesterol Profiles due to the Incorporation of Salvinia molesta in the Diets of Kampong Chicken - A. Setiadi; S. I. Santoso; B. M. Setiawan; S. Nurfadillah; H. Sasana; K. Prayoga; S. Susanti (Tropical Animal Science Journal, 2020)
This study aimed to perform an assessment of economic performance and meat cholesterol profiles of Kampong chickens fed diets with the increasing levels of Salvinia molesta. One hundred male Kampong chickens were divided into 4 treatments containing 0% (T0), 6% (T1), 12% (T2), and 18% (T3) of S. molesta leaf (SML) in the diet. Then, an economic analysis was performed by calculating revenue, feed cost, and income over feed cost (IOFC). Investment analysis was computed when the farmers raised 1000 heads of Kampong Chicken utilized SML in the feed. NPV, PP, and B/C ratio were calculated for each treatment. The performance of the Kampong chickens fed the diet with SML content of 18% gave the best feed consumption, the final weight, and FCR. Kampong chickens fed diet with SML content of 18% gave the best IOFC. In the investment analysis, the Kampong chicken fed diet contained 18% SML gave the best NPV, PP, and B/C ratio. Regression analysis was conducted on the level of SML in the diet of kampong chicken on some parameters. Kampong chicken fed diet contained SML had significantly higher HDL and lower LDL concentrations. The optimum inclusion level of SML leading to a reduced feed cost and increased IOFC, as well as feasibility, was 18%. Based on the study, utilization of SML up to 18% in the diet of kampong chicken technically and economically gave the best performances.